Navigating the ‘grey zone’: academic collaboration and research on/in Russia during geopolitical crisis - Nielsen, Henrik Dorf; Kaisto, Virpi (Fennia - International Journal of Geography, 2024)
Russia’s illegal annexation of Crimea in 2014 and attack on Ukraine in 2022 have led to widespread sanctions being placed on Russia by the European Union, including sanctions related to academic cooperation. National governments, supranational bodies, science academies and research institutions as well as publishers have likewise formed policies suspending and restricting collaboration regarding Russia-related research. These policies are, however, not straight forward and there are many practical and ethical questions that individual researchers must ask themselves. At Finnish Geography Days 2023 in Joensuu, a panel was dedicated to discussing some of these questions. This article summarizes main themes discussed during the panel and sheds light on the multiple ways researchers experience and navigate the ‘grey zone’ of academic collaboration and research on/in Russia in the current geopolitical context. The article emphasizes the necessity of further discussing the effectiveness and impact of the sanctions and restrictions: Are they reasonable? Who benefits from them, and who suffers?